Kinetics of Physiological Responses as a Measure of Intensity and Hydration Status During Experimental Physical Stress in Human Volunteers - Kartaram, Shirley W.; van Norren, Klaske; Schoen, Eric; Teunis, Marc; Mensink, Marco; Verschuren, Martie; M’Rabet, Laura; Besseling-van der Vaart, Isolde; Mohrmann, Karin; Wittink, Harriet; Garssen, Johan; Witkamp, Renger; et al. (Frontiers in Physiology, 2020)
Introduction: The possibility to evaluate resilience in relation to a stressor as a measure for individuals’ health status is relevant. Physical exercise is a well-known stressor to challenge homeostasis. The dynamic responses and kinetic changes of biomarkers for intestinal, immunological, and metabolic processes following moderate and strenuous exercise can be used to study physiological resilience and responsiveness to interfering factors such as mild dehydration. Aim: To investigate the kinetics of the physiological responses to moderate and high intensity exercise, including a mild dehydrated condition, in a bicycle ergometer test. Methods: Fifteen healthy and fit men (20-35 years, VO2max 56.9 ± 3.9 ml kg−1 min−1) started with a rest protocol (protocol 1) and subsequently performed (in a cross-over design) four cycling protocols of 1 hour (protocols 2-5) at different intensities: 70% Wmax in hydrated (protocol 2) and dehydrated state (protocol 3), 50% Wmax (protocol 4) and intermittent 85/55% Wmax in blocks of 2 min (protocol 5). Individual maximum workload was pre-assessed, the wash out period between the protocols was 1 week. Parameters of different physiological domains were measured in blood samples that were collected both before and during exercise and at various timepoints up to 24 hours afterwards. Data was analyzed using a multilevel mixed linear model with multiple test correction. Results: Kinetic changes of various biomarkers showed exercise-intensity-dependent responses. These include parameters indicative of metabolic activity (e.g. creatinine, bicarbonate), immunological and hematological functionality (e.g. leukocytes, hemoglobin) and intestinal physiology (citrulline, intestinal fatty acid binding protein, zonulin). In general, responses to high intensity exercise of 70% Wmax and intermittent exercise i.e. 55/85% Wmax were more pronounced compared to exercise at 50% Wmax. Cycling at high intensity in a dehydrated condition was perceived significantly more exhausting (18, rated on the Borg scale from 0-20) and showed intensified responses. Conclusion: The response kinetics of crucial physiological parameters were clearly dependent on exercise intensity and hydration status. The effects of dehydration suggest that the exercise model can potentially be applied to examine effects of other factors including nutritional status and disease. Future studies are needed for standardization, also for various groups such as elderly.